(untitled) (International Seven Journal of Multidisciplinary, 2022)
The advancement of mega hair technologies has increasingly incorporated dermatological and biomechanical principles to address the needs of individuals with sensitive scalps or partial to complete absence of natural hair. Traditional high-tension extension methods have been associated with follicular stress and traction-related alopecia, prompting the development of safer, low-tension alternatives. This article examines modern traction-free and scalp-preserving mega hair techniques, including tape-based systems, clip-in extensions, halo designs, micro-attachments, and lace-based hair prostheses. Emphasis is placed on mechanical load distribution, material biocompatibility, and biomimetic design as key factors in reducing dermatological risk while maintaining aesthetic realism. By integrating knowledge from cosmetology, dermatology, and material science, contemporary mega hair solutions offer improved comfort, safety, and inclusivity. The findings highlight the importance of individualized scalp assessment, professional application, and routine maintenance to ensure long-term scalp health and user well-being.